First record of Corticeus bicolor (Olivier, 1790) (Coleoptera, Tenebrionidae) from Kazakhstan - Izbasar I. Temreshev (Acta Biologica Sibirica, 2024)
The darkling beetle (Coleoptera: Tenebrionidae) Corticeus bicolor (Olivier, 1790) is recorded for Kazakhstan for the first time. The species was found in gallery of bark beetles Anisandrus dispar Fabricius, 1792, Scolytus intricatus Ratzeburg, 1837 and Xyleborinus saxeseni (Ratzeburg, 1837) in Akmola and Kostanai oblasts. A key to known species of the genus Corticeus Piller & Mitterpacher, 1783 from Kazakhstan is given.